Compreendendo o papel da melamina (C3H6N6) no caminho de degradação de compósitos fertilizantes contendo ureia - Rodrigues, Joyce Fabiula (Universidade Federal de São Carlos, 2021)
This work proposed a study of new fertilizer composites that have melamine in their composition, a molecule of high nitrogen content (66% total mass) but recalcitrant, observing factors that may influence the effective release of its N as a nutrient. Composites with thermoplastic starch (TPS) matrix of urea and melamine were studied for fertilizer application. The composites (TPS:Ur:Mel 1:2 and TPS:Ur:Mel 2:1) produced were characterized by X-ray diffractometry, absorption in the infrared region and scanning electron microscopy and tested with the presence of microorganisms to study behavior in the presence of melamine. All characterizations indicated the synergy between the precursors in the extrusion process. The urea release tests showed superior results for composites compared to pure urea. In addition, tests with the addition of the microorganisms Trichoderma Harzianum and Acidovorax Citrulli led to a better understanding of the melamine biodegradation process. As expected, the use of microorganisms accelerated the releases, but played an important role in terms of comparison with the use in soils without controlled conditions. The microorganisms adapted to the presence of melamine and the quantitative results of the release of ammonia, ammonium and nitrate gases indicated that the melamine degradation process was probably initiated. Such tests highlighted the efficiency of the use of microorganisms so that the N present in melamine is accessible, and corroborated the ability of controlled release of polymeric composites synthesized with starch matrix
Understanding the role of melamine (C3H6N6) in the degradation path of fertilizing composites containing urea
Keywords: Nitrogênio; Melamina; Compósito nitrogenado; Degradação biólogica; Nitrogen; Melamine; Nitrogen composite; Biological degradation; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES